Toward the assessment of the work-family interface - Tement, Sara (Psihološka obzorja (Ljubljana), 2010)
Research on the work-family interface has gained importance especially because of the changing composition of the working population and the rapidly changing working environment worldwide. However, there are no appropriate questionnaires available that would address negative and positive experiences of the work-family interface. Therefore, a study has been conducted in order to validate two existing scales measuring work-family conflict and work-family enrichment. The dimensionality, item adequacy, reliability, and construct validity were addressed by means of a sample of 214 employees from Slovenian enterprises and institutions. The results for the Slovenian scales confirmed the multiple dimensions of the original versions. Support was also found for acceptable reliability and construct validity of the two scales. Although some limitations were noticed, the scales represent an important step in examining the work-family interface of the Slovenian workforce.
Keywords: delo; labour; družina; family; konflikti; veljavnost; psihološko testiranje